Stability and In vitro Comparative Study of Optimized Non-Aqueous Nano Emulsion of Naproxen with Marketed Formulations (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: The current study’s objective was to evaluate stability study and compare and analyze the improved nonaqueousnanoemulsion (NANE) of naproxen with marketed gel formulations (M1 and M2). Methods: Utilizinga low energy emulsification technique, an optimized NANE of naproxen was prepared. The comparison researchwas assessed for general appearance, pH, viscosity, drug content, and in vitro drug release against marketedformulations. Six months of stability investigations were carried out as per ICH Q1A R2 guideline. Duringstability study, phase separation, creaming, cracking, phase inversion, color, pH, viscosity, and drug contentwere evaluated. Results: In comparative study, pH of NANE and marketed formulations M1 and M2 was foundto be 5.5 ± 0.36, 5.8 ± 0.80, and 5.6 ± 0.08, respectively. Viscosity is a crucial characteristic of NANE; it wasfound that optimized NANE showed lower viscosity (54.40 ± 1.25 mPa.S) than marketed formulations (M1-78.20 ± 0.76 mPa.S, M2-80.56 ± 0.28 mPa.S). Drug content of NANE of naproxen and marketed formulationswas found to be 95 ± 0.46, 98 ± 0.16, and 97 ± 0.38, respectively. From the in vitro drug release study, we foundthat optimized NANEs of naproxen showed highest percentage of drug release (96.24 ± 1.96) as compared tomarketed formulation M1 (90.58 ± 1.31) and M2 (89.15 ± 1.33), respectively. No phase separation, creaming,cracking and phase inversion was seen after agitation, centrifugation, and freeze-thaw cycles. This demonstratedthe NANE excellent stability in the presence of gravity. pH and drug content of NANE was stable within 6 monthsof stability study. Viscosity of optimized NANEs decreased from 55.80 ± 0.48 mPa.S to 51.20 ± 1.06 mPa.S within6 months in accelerated stability study and stable in intermediate stability study. Conclusion: It was discoveredfollowing a stability assessment that there was no indication of instability.